2007
DOI: 10.1105/tpc.107.053678
|View full text |Cite
|
Sign up to set email alerts
|

The MYB46 Transcription Factor Is a Direct Target of SND1 and Regulates Secondary Wall Biosynthesis in Arabidopsis

Abstract: We demonstrate that the Arabidopsis thaliana MYB46 transcription factor is a direct target of SECONDARY WALL-ASSOCI-ATED NAC DOMAIN PROTEIN1 (SND1), which is a key transcriptional activator regulating the developmental program of secondary wall biosynthesis. The MYB46 gene is expressed predominantly in fibers and vessels in stems, and its encoded protein is targeted to the nucleus and can activate transcription. MYB46 gene expression was shown to be regulated by SND1, and transactivation analysis demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
527
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(559 citation statements)
references
References 31 publications
(50 reference statements)
15
527
0
5
Order By: Relevance
“…AtMYB58, AtMYB63 and AtMYB85 activated lignin biosynthesis in fibers and/or vessels (Zhou et al 2009). AtMYB46 is found to be a positive regulator of lignin biosynthesis in fibers and vessels and also regulated cellulose and xylan deposition (Zhong et al 2007). AtMYB26/ MS35 controlled secondary wall deposition in anthers (Yang et al 2007).…”
Section: Regulation Of Primary and Secondary Metabolismmentioning
confidence: 99%
“…AtMYB58, AtMYB63 and AtMYB85 activated lignin biosynthesis in fibers and/or vessels (Zhou et al 2009). AtMYB46 is found to be a positive regulator of lignin biosynthesis in fibers and vessels and also regulated cellulose and xylan deposition (Zhong et al 2007). AtMYB26/ MS35 controlled secondary wall deposition in anthers (Yang et al 2007).…”
Section: Regulation Of Primary and Secondary Metabolismmentioning
confidence: 99%
“…In particular, genes encoding cellulose synthases that function specifically in the synthesis of the secondary cell wall, including CESA4/IRX5, CESA7/IRX3, and CESA8/IRX1 (Taylor et al, 2003), were upregulated by both VND6 and SND1 (see Supplemental Data Set 1 online). Secondary wall synthesis is regulated by a number of MYB transcription factors (Zhong et al, 2007(Zhong et al, , 2008Zhou et al, 2009). In our experiments, MYB46, MYB83, and MYB103 were upregulated by VND6 and SND1 (see Supplemental Data Set 1 online).…”
Section: Identifying the Genes Downstream Of Vnd6 And Snd1 With Micromentioning
confidence: 99%
“…Molecular studies of SND1 indicated that a network of transcription factors function downstream of SND1 and finally lead to secondary cell wall formation (Zhong et al, 2007(Zhong et al, , 2008Zhou et al, 2009). SND1 directly regulates the expression of genes encoding the transcription factors MYB46, MYB83, MYB103, SND3, and KNAT7 (Zhong et al, 2007;McCarthy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En plantas, algunos factores de transcripción MYB participan en la activación de genes de respuesta a estrés biótico (Hirayama y Shinozaki, 2010), tales como infección por patógenos (Vailleau et al, 2002); en la regulación del metabolismo primario y secundario, como el control de la acumulación de flavonoles (Stracke et al, 2007), biosíntesis de antocianinas (González et al, 2008), el desarrollo del polen (Preston et al, 2004), la biosíntesis de lignina (Newman et al, 2004;Zhou et al, 2009;Zhong et al, 2007Zhong et al, , 2008 y la apertura estomática (Liang et al, 2005), entre otras. Sin embargo también se ha encontrado su participación en mecanismos de respuesta a estrés abiótico (Alves et al, 2015;.…”
Section: Factores De Transcripción Mybunclassified